(3CeKGd GdMOjKs - (3Hf NdGO , GdMSf Hf YHO GdQMef Hf NdGO GdQGegQeRj, CHh eMeO,J (B360 (3g` s
(3ChdgG (B:s
(3gPG PcQ GdCeKGd GdeQhjI Yf GdfHi Udi Gddg Ydjg hSde , hgj Ydi NdGa eG QhjfGg ef cdGeg GdeTGcd ddCeKGd GdePchQI Yf eJbOSi GdYQH s
(3BNQgG (B:s
(3jfJgi HJaSjQ bhdg Udi Gddg Ydjg hSde (B" (3GdhdO eLHfI eHNdI (B" : ( (3bGd (B: (3CHh eMeO QMeg Gdgd , gPGf eUOQGf ef GdHNd hGdLHf hYf dbGA GdYOO ETfGbkG ef GdeVjYI dge BNQ GdcJGH , hGdMeO ddg QH GdYGdejf (B) s
(3GdfSNI HgG MhGTs
(3Ydi GdhQbI GdTGFbI Ydi GdYfhGf bQGAI TjN GdESdGe GHf MLQ GdcJGH Ydi aGWeI HfJ GdHNGQis
(3hai UOQ GdLRA GdSGHY bQGAI hSeGY hJUMjM Pdc Ydi GHQGgje Hf YdGA GdOjf GdebQTi GdTGaYi GdbdbTfOis
(3hai BNQI ebGHdI HCUd Ydjg NW GdMGaX GdSdai ai YOI CeGcf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B235s
Keywords: (3GdMOjK h GdeUWdMs